2014
DOI: 10.1371/journal.pone.0108289
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Cells with the IDH1 Mutation Modulate Metabolic Fractional Flux through Pyruvate Carboxylase

Abstract: BackgroundOver 70% of low-grade gliomas carry a heterozygous R132H mutation in the gene coding for isocitrate dehydrogenase 1 (IDH1). This confers the enzyme with the novel ability to convert α-ketoglutarate to 2-hydroxyglutarate, ultimately leading to tumorigenesis. The major source of 2-hydroxyglutarate production is glutamine, which, in cancer, is also a source for tricarboxylic acid cycle (TCA) anaplerosis. An alternate source of anaplerosis is pyruvate flux via pyruvate carboxylase (PC), which is a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 37 publications
7
61
0
Order By: Relevance
“…Tracer studies show that SDH-null cells produce citrate predominantly through reductive carboxylation of Gln and accumulate Gln-derived succinate, a product inhibitor of the ␣-KG-dependent dioxygenases, while relying on PC for anaplerosis and synthesis of aspartate to support nucleotide biosynthesis required for proliferation (59,86,87). Likewise, IDH1 mutant cells increased conversion of [ 13 C 1 -2]Glc to PC-derived [ 13 C 1 -3]Glu, which implicates the importance of PC anaplerosis for proliferation of these cells (88). More intriguingly, PC expression and in vivo activity were enhanced in human NSCLC tumors relative to adjacent non-cancerous lung tissues, and silencing PC expression in lung cancer lines slowed tumor growth in mouse xenografts (8,53 (89).…”
Section: Applications Of Sirm In Drug Developmentmentioning
confidence: 86%
“…Tracer studies show that SDH-null cells produce citrate predominantly through reductive carboxylation of Gln and accumulate Gln-derived succinate, a product inhibitor of the ␣-KG-dependent dioxygenases, while relying on PC for anaplerosis and synthesis of aspartate to support nucleotide biosynthesis required for proliferation (59,86,87). Likewise, IDH1 mutant cells increased conversion of [ 13 C 1 -2]Glc to PC-derived [ 13 C 1 -3]Glu, which implicates the importance of PC anaplerosis for proliferation of these cells (88). More intriguingly, PC expression and in vivo activity were enhanced in human NSCLC tumors relative to adjacent non-cancerous lung tissues, and silencing PC expression in lung cancer lines slowed tumor growth in mouse xenografts (8,53 (89).…”
Section: Applications Of Sirm In Drug Developmentmentioning
confidence: 86%
“…Cells (2 Â 10 6 ) were lyzed in Ripa buffer (Cell Signaling Technology) containing PhosSTOP Phosphatase Inhibitor Cocktail Tablets (Roche) and cOmplete ULTRA Tablets (Roche), and processed as previously described (24). A spectrophotometric reading in kinetic mode at 412 nm was taken for 10 minutes at 30 C (Ultrospec 2100pro, GE Healthcare Life Sciences) and data normalized for protein content.…”
Section: Pyruvate Carboxylase Activitymentioning
confidence: 99%
“…Furthermore, in vivo tracing studies in an orthotopic model of human glioblastoma using 13C-labeled glucose have indicated that pyruvate carboxylase and PDH are highly active in GBM (Marin-Valencia et al, 2012). One recent study demonstrated that IDH mutant overexpression in astrocytes results in an increased fractional flux through pyruvate carboxylase and an increase in PC expression, suggesting this pathway is critical for IDH mutant cells to maintain TCA activity (Izquierdo-Garcia et al, 2014). Consistent with this observation, we observed increased pyruvate cycling through malic enzymes and PC in HCT116 cells harboring heterozygous IDH1 mutations (Grassian et al, 2014).…”
Section: Glucose Metabolismmentioning
confidence: 99%